Visualization Analysis on the Current Status and Development Trend of Geothermal Research: Insights Into the Database of Web of Science - Wan, Xiao-fan; Zhang, Hao; Shen, Chuan-bo (Frontiers in Energy Research, 2022)
Geothermal energy is considered a renewable, clean, and environmentally friendly energy source. In addition, it is efficient and relatively cost effective. Therefore, the demand for the development and utilisation of geothermal resources is increasing annually. To understand the current status and developments within the context of geothermal research, quantitative and qualitative analyses were carried out by combining two visualisation software, namely, VOSviewer and CiteSpace; this analysis also entailed the secondary development of R language. The results showed that the USA, China, and Germany are the main contributors to geothermal research. We also found that geothermal research hot spots encompass five geothermal research clusters, such as, renewable energy utilisation, heat flow, numerical simulation, geochemistry, and groundwater. In addition, the strategic diagram and thematic structure revealed how geothermal research has evolved over time. Finally, the timeline view and burst term highlight the possible frontiers of geothermal power generation, enhanced geothermal systems, and ecological environment protection. These insights will provide scholars and policymakers with a systematic understanding of the current research and directions for future studies.